Prolonged parallel chronology of distinct TTG types in the Lake Inari terrain, Arctic Fennoscandia: Implications for stratified stationary plume-related source - Joshi, Kumar Batuk; Halla, Jaana; Kurhila, Matti; Heilimo, Esa (Elsevier Scientific Publ. Co, 2024)
Revealing Archean crust-formation processes requires understanding of geochemical and chronological differences in granitoids. During the early evolution of Earth's felsic crust, large amounts of tonalite-trondhjemite-granodiorites (TTGs) were formed, making up most of the Archaean crust preserved until today. The TTGs have two geochemical endmembers, the low- and high-HREE (heavy rare earth elements) TTGs. The genesis of TTGs has been explained by dehydration melting of basaltic crust, but the formation of different types of TTGs is not well understood. This study provides new U–Pb zircon ages for deciphering the temporal relationships between different TTG types in the Lake Inari terrain, Arctic Fennoscandia. The interpretation of the FIRE (Finnish Reflection Experiment) 4A line shows the existence of two tectonic blocks for the terrain. Our results from zircon populations of low- and high-HREE TTGs and adjacent porphyritic granitoids show a large time spread suggesting a prolonged migmatization in the Lake Inari terrain from 2900 to 2600 Ma. This supports a rather long-term source of heat such as a stationary plume related to stagnant or sluggish lid -tectonics. The high- and low-HREE TTGs show parallel ages and occur intermingled, which points to a common geochemically stratified source instead of different tectonic settings. There is no distinct age difference between two tectonic blocks identified in the FIRE 4A seismic reflection profile. Prolonged melting episodes of thickened felsic crustal horizon produced porphyritic granites between 2650–2500 Ma. The ~1.9 Ga Lapland Kola orogeny caused minor zircon recrystallization but did not influence Archaean migmatite morphology. The Lake Inari TTGs peak approximately at. 2.8 Ga, i.e., 100 Ma before the formation of the alleged Kenorland supercontinent. Peer reviewed